2019
DOI: 10.2478/bog-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

Capacities of African-oriented Polish NGOs: a quantitative approach

Abstract: The aim of the paper is to investigate the capacity of Polish non-governmental organisations implementing development projects in Africa. Drawing on an integrated systemic perspective of capacity that recognises internal and external factors, this paper focuses on internal factors. Using a quantitative approach to operationalise capacity, the study suggests that those non-governmental organisations implementing the Polish development policy in Africa are highly polarised and can be divided in two groups. Whils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Some studies have found interest groups based on different factors to those commented on above. For example, the study by Frankowska, Łęcka, and Frankowski [96] found that the NGOs that implement Poland's development policy in Africa are highly polarized and can be divided into two groups according to their capacities. The first consists of two large organizations with a long history and the capacity to raise funds internationally, and the second consists of smaller NGOs with different capacities and working strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found interest groups based on different factors to those commented on above. For example, the study by Frankowska, Łęcka, and Frankowski [96] found that the NGOs that implement Poland's development policy in Africa are highly polarized and can be divided into two groups according to their capacities. The first consists of two large organizations with a long history and the capacity to raise funds internationally, and the second consists of smaller NGOs with different capacities and working strategies.…”
Section: Discussionmentioning
confidence: 99%